2004
DOI: 10.1016/s0896-6273(03)00814-6
|View full text |Cite
|
Sign up to set email alerts
|

Extensive and Divergent Effects of Sleep and Wakefulness on Brain Gene Expression

Abstract: Sleep is present in all species where it has been studied, but its functions remain unknown. To investigate what benefits sleep may bring at the cellular level, we profiled gene expression in awake and sleeping rats by using high-density microarrays. We find that approximately 10% of the transcripts in the cerebral cortex change their expression between day and night and demonstrate that half of them are modulated by sleep and wakefulness independent of time of day. We also show that molecular correlates of sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

63
598
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 566 publications
(662 citation statements)
references
References 53 publications
63
598
1
Order By: Relevance
“…The detection of unique spots in each of the experimental groups provides the first evidence that alterations in protein profiles underlie spontaneous sleep-wake bouts. In addition, the percentages of state-related SYPRO Ruby expression were comparable to those reported for cortical mRNA profiles from rats sacrificed after several hours of spontaneous sleep [albeit, in the same portion of the lights-on period as our studies; Cirelli et al, 2004], suggesting that the intracellular response to sleep and waking impacts small subsets of both total cellular protein and mRNA. The analysis of phosphorylated spots suggested that cellular activities also varied across spontaneous sleep-wake states (Fig.…”
supporting
confidence: 84%
See 4 more Smart Citations
“…The detection of unique spots in each of the experimental groups provides the first evidence that alterations in protein profiles underlie spontaneous sleep-wake bouts. In addition, the percentages of state-related SYPRO Ruby expression were comparable to those reported for cortical mRNA profiles from rats sacrificed after several hours of spontaneous sleep [albeit, in the same portion of the lights-on period as our studies; Cirelli et al, 2004], suggesting that the intracellular response to sleep and waking impacts small subsets of both total cellular protein and mRNA. The analysis of phosphorylated spots suggested that cellular activities also varied across spontaneous sleep-wake states (Fig.…”
supporting
confidence: 84%
“…More recent microarray analyses showed that a small percentage of genes (i.e., 1-5%) were differentially expressed across sleep and waking states, independent of the time of day (TOD) or the brain region studied [Cirelli et al, 2004;Terao et al, 2006]. These patterns were conserved across rodent species [Terao et al, 2006] and encoded proteins associated with a variety of housekeeping functions, including energy metabolism, synaptic plasticity, membrane trafficking and maintenance, and cholesterol biosynthesis [Cirelli et al, 2004;Terao et al, 2006].…”
Section: Abstract: Two-dimensional Electrophoresis (2de); Mass Spectmentioning
confidence: 99%
See 3 more Smart Citations